Student Motivation in Using Volleyball Learning Media Seen From Gender Perspective - Vhiyona Suchie Nophiyani Ramadhan; Bambang Gatot Sugiarto; Dhani Agusni (Journal of Physical and Outdoor Education, 2025)
This study aims to analyze students' motivation in using volleyball learning media from a gender perspective. The focus of this research is to identify differences in motivation between male and female students in learning volleyball by utilizing various types of media, such as visual, audio, and audiovisual. This study employs a qualitative descriptive method with a mixed approach. The instruments used include questionnaires and observations of 30 eighth-grade students from SMP Negeri 15 Bandung, selected through random sampling. The results indicate that the use of learning media positively influences students' learning motivation. Audiovisual media has been proven to be the most effective in increasing students' interest and engagement, regardless of gender, although there are differences in responses based on gender. This research emphasizes the importance of implementing inclusive and gender sensitive learning media to enhance the effectiveness of physical education learning, particularly in volleyball. Theuse of diverse and inclusive learning media significantly boosts students' motivation in volleyball lessons. To achieve optimal results, learning media should be tailored to students' gender characteristics to make the learning process more engaging, fair, and effective.